AN ETHNOGRAPHIC STUDY ON THE PERCEIVED SPIRITUAL CAUSES OF PSYCHOSIS IN CENTRAL UGANDA. - Atim, Elizabeth; Tukei, Maurice Osire (Student's Journal of Health Research Africa, 2023)
Background The WHO defines health as the complete physical, mental, and social well-being and not simply the absence of disease. Unfortunately, many are increasingly suffering from mental illness especially following the recent COVID-19 pandemic characterized by psychosis among other symptoms. According to the DSM-5, psychosis is characterized by the following: “delusions, hallucinations, disorganized speech, catatonia or abnormal motor behaviour, and negative symptoms” which greatly disrupt human life and relationships. Although there are conventional ways of managing psychosis, people still seek spiritual modalities due to the perceived spiritual causes. This study, therefore, sought to identify and document the perceived spiritual causes of psychosis in Central Uganda from July to December 2022. Methodology An ethnographic study design was employed for this explorative qualitative study. The sample size was 15 which was obtained through saturation. Sampling was carried out using the snowball method and the respondents were traditional healers, Christians, and Muslims who practiced spiritual management of psychosis as well as their clients (patients and caregivers). In-depth Interviews and Key informant interviews as well as observations were used for data collection. Data were analysed thematically. Results The spiritual cause of Psychosis in the study area was found to be demons (evil spirits). These were either ancestral in nature or a result of witchcraft. Witchcraft was either sent or self-inflicted. Conclusion There is a spiritual world that can influence and inflict disease in the physical body including mental illness (psychosis). Recommendation Research needs to be done to establish whether the disease progress and manifestations are similar in one who has psychosis as a result of spiritual causes compared to one whose psychotic symptoms are a result of purely physical causes.